Note on the relations of the supposed carboniferous plants of Bear Island with the paleozoic flora of North America [electronic resource] ([S.l. : s.n., 1873)
Printed ephemera. Caption title. "(From the Quarterly Journal of the Geological Society for February 1873]." Electronic reproduction. Mode of access: Internet. 44